THE RELATIONSHIP OF SECTIO CAESAREA DELIVERY AND THE INCIDENT OF NEONATAL JAUNDICE IN NEONATES AT WAJAK HUSADA MALANG GENERAL HOSPITAL: HUBUNGAN PERSALINAN SECTIO CAESAREA DENGAN KEJADIAN NEONATAL JAUNDICE PADA NEONATUS DI RUMAH SAKIT UMUM WAJAK HUSADA MALANG - Mega Sanjaya; Rifzul Maulina; Nila Widya Keswara (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Introduction: The incidence of neonatal jaundice at Wajak Husada General Hospital, Malang, was recorded to increase in 2023. In the same year, cesarean section deliveries (SC deliveries) at Wajak Husada General Hospital also increased. However, the results of previous research regarding the relationship between SC delivery and the incidence of neonatal jaundice still need to be found. This study aimed to determine the relationship between SC delivery and the incidence of neonatal jaundice in neonates at RSU Wajak Husada in 2023. Methods: This research was an analytical observational study with a cross-sectional design. Sampling in this study used a case-control technique with a sample size of 172 neonates. Results: Crosstabulation results showed that more respondents from the neonatal jaundice group (66.7%) had a CS delivery status than those without neonatal jaundice (28.9%). The chi-square test results showed that the status of SC delivery and the incidence of neonatal jaundice had a p-value of 0.000. The OR calculation results showed that respondents with a history of SC delivery were 4.909 times more likely to experience neonatal jaundice than those with a history of natural delivery (95% CI 2.556 – 9.428). Conclusion: There is a relationship between SC delivery and the incidence of neonatal jaundice in neonates at RSU Wajak Husada in 2023.